UPAYA PENINGKATAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI MATERI MEMECAHKAN MASALAH MEMBACA DATA STSTISTIK DALAM MATA PELAJARAN EKONOMI MELALUI MODEL PEMBELAJARAN JIGSAW, KELAS X IPS 2 SEMESTER GANJIL DI SMA NEGERI 3 KOTABUMI TAHUN PELAJARAN 20 - emawati emawati (Universitas Muhammadiyah Kotabumi, 2020)
SMA Negeri 3 Kotabumi as an educational institution has the problem of still low student learning outcomes in Economics. Student learning outcomes in economic subjects, especially students of class X IPS 2 are still low. Determination of learning strategies in order to improve the quality of the process and learning outcomes can be investigated by classroom action research, because this study aims to overcome problems or solve problems in the classroom by taking action. One of the cooperative learning techniques is the Jigsaw technique. By implementing Cooperative Learning procedures correctly, it will be able to activate students so that they can improve student learning outcomes Classroom Action Research (CAR) is designed as a study material in the application of learning